Od Osoby Ojca w misterium Trójjedynego Boga do człowieka jako osoby. Ontologia komunijna Joannisa Zizioulasa - Mariusz Jagielski (Studia Paradyskie)
How essential is the connection between the Trinitarian dogma and theological anthropology? John Zizioulas shows the connection in his communal ontology, beginning with the Person of the Father in the mystery of the Trinity as a foundation for describing being. This way, he can present man as an imago Dei, or, actually, as an imago Trinitatis. Describing man as a person in God’s image entails, therefore, showing him both as hypostasis and as ekstasis. Experiencing in his death the drama of individualization and the risk of nothingness as the fruit of his fall, man can find in Christ his communal fulfilment as a person.